THE AVERAGE AND MARGINAL COST OF CAPITAL (World Bulletin of Management and Law, 2024)
A cost of various source of financing is different, the financial manager can vary capital structure in order to minimize expenses on its attraction for achievement big efficiency of the enterprise activity. Thus the unit of the cumulative capital (for example, 1 sum) will actually consist from several components, each of which has its own price. As it has been shown earlier, the given price represents the rate of profitableness demanded by that or other supplier (owner) of the capital. Thus, each unit of the capital enclosed in economic activities, should provide such level of profitableness which would satisfy its all owners separate a component
Keywords: The value of the enterprise; the cost of capital; the structure of capital